1975
DOI: 10.1007/bf00584540
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sodium excretion in response to infusion of isotonic saline into the vena porta and vena cava of conscious rats

Abstract: 1. Indwelling non-occlusive catheters were placed in the vena porta and inferior vena cava of female rats several days before experimentation. Isotonic saline or isosmotic glucose (2% of body wt.) was infused into one vein followed one to several days later with an identical infusion into the other vein of each conscious animal. 2. Significantly higher urine flow and sodium excretion resulted from infusion of isotonic saline (0.5 ml/min) into the vena porta than into the vena cava. Modest prehydration or secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Experimental evidence for the existence of hepatic sodium sensors has been reported by demonstrating that the natriuretic response to a saline load is greater when sodium chloride is given into the portal vein than into a systemic vein (Daly et al 1967, Potkey & Gilmore 1970, Strandhoy & Williamsson 1970, Passo et a/. 1973, Perlmutt et al 1975, although these observations could not be confirmed in other similar studies (Schneider et al 1970, Glasby & Ramsay 1974, Kapteina et al 1978. The amount of saline infused in these experiments seems very high evoking unduly large increases of portal sodium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence for the existence of hepatic sodium sensors has been reported by demonstrating that the natriuretic response to a saline load is greater when sodium chloride is given into the portal vein than into a systemic vein (Daly et al 1967, Potkey & Gilmore 1970, Strandhoy & Williamsson 1970, Passo et a/. 1973, Perlmutt et al 1975, although these observations could not be confirmed in other similar studies (Schneider et al 1970, Glasby & Ramsay 1974, Kapteina et al 1978. The amount of saline infused in these experiments seems very high evoking unduly large increases of portal sodium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the episodical nature of salt consumption intrinsically generates short-term imbalances. Thus, it is currently believed that the introduction of salt into the lumen of the intestine triggers two protective mechanisms: one that slows the absorption of the ingested salt from the lumen (40), and another that accelerates the excretion of systemic salt by the kidney (1)(2)(3)(4)(5)(6). Together, these mechanisms minimize, or "buffer," the impact of an incoming salt load.…”
Section: A Working Model For the Biological Roles Of Prougn In Healthmentioning
confidence: 99%
“…This has contributed to the concept of an enterorenal axis for solute homeostasis that is thought to preempt the slower volume-dependent responses, such as those mediated by atrial natriuretic peptide (ANP), angiotensin, aldosterone, and renal perfusion pressure. Several mechanisms probably contribute to enhanced postprandial natriuretic activity, among which the most often invoked are neuronal or humoral reflexes initiated by salt sensitive chemoreceptors in the portal vein (5)(6)(7)(8)(9), and an endocrine axis in which natriuretic peptides are released into the circulation from the intestine in response to salt intake (10).…”
mentioning
confidence: 99%
“…This apparent discrepancy may result from the different experimental procedures or perhaps from differences in the level and the extent of visceral denervation. Although the hepatic branch of the vagus nerve in the rat has been reported to include an osmosensitive component (Niijima, 1969) and transection of the hepatic vagus has been reported to eliminate the hepatogenic diuresis induced by simultaneous infusion of water into the hepatic-portal vein and of 1.8% NaCI into the vena cava (Dennhardt et al, 1971), this selective denervation did not abolish the greater urine flow and sodium excretion induced by hepatic-portal infusion of an isotonic saline load relative to caval infusion (perlmutt, Aziz, & Haberich, 1975). And hepatic vagotomy did not impair spontaneous drinking or responsiveness to osmotic and volemic regulatory challenges in rats (Martin, 1981).…”
Section: Discussionmentioning
confidence: 99%